2016
DOI: 10.1038/ncomms13179
|View full text |Cite
|
Sign up to set email alerts
|

NIN-like protein 8 is a master regulator of nitrate-promoted seed germination in Arabidopsis

Abstract: Seeds respond to multiple different environmental stimuli that regulate germination. Nitrate stimulates germination in many plants but how it does so remains unclear. Here we show that the Arabidopsis NIN-like protein 8 (NLP8) is essential for nitrate-promoted seed germination. Seed germination in nlp8 loss-of-function mutants does not respond to nitrate. NLP8 functions even in a nitrate reductase-deficient mutant background, and the requirement for NLP8 is conserved among Arabidopsis accessions. NLP8 reduces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
173
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(180 citation statements)
references
References 51 publications
6
173
0
1
Order By: Relevance
“…We identified transcription factor modules that control modules of processes and also identified a novel root architecture role for NLP8 (Yan et al, 2016) and a new root architecture-regulating transcription factor, WRKY15, the functions of which are moderated by N abundance. The molecular regulation that we uncover underlies lateral root developmental responses under different environments, one component of root plasticity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We identified transcription factor modules that control modules of processes and also identified a novel root architecture role for NLP8 (Yan et al, 2016) and a new root architecture-regulating transcription factor, WRKY15, the functions of which are moderated by N abundance. The molecular regulation that we uncover underlies lateral root developmental responses under different environments, one component of root plasticity.…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed T-DNA lines and found that a nlp8 homozygous loss of expression knockout mutant (nlp8-2 as named in Yan et al, 2016) has a shorter primary root and fewer lateral roots on replete levels of nitrate ( Figure 2F; Supplemental Data Set 3) but not on depleted levels of nitrate. This is consistent with findings by Yan et al (2016) who did not analyze root development but did observe N-dependent effects on germination.…”
Section: Reprogramming Of Cell-type Responses After Nitrogen Influxmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the NLP8-mediated response is thought to be independent of NO signaling and a direct response to nitrate, because NO-defective mutant seeds still respond to nitrate and germinate in a NLP8-dependent manner (Yan et al, 2016). The nitrate and NO signaling pathways seem to target different transcription factors in seeds.…”
Section: New Players In Nitrate and Nitric Oxide Signaling In Seedsmentioning
confidence: 99%